Hermeneutics and the Qur’anic Texts in the intellectual linguistic Context - Mohd Noor, Ahmad Yunus; Sahrir, Muhammad Sabri (2011)
Hermeneutical approach in dealing with the Qur’an as the holy book of Islam is wanted to be adopted by Muslims. Indeed, the issue of Qur’anic hermeneutics can illustrate this dimension of the meaning of hermeneia. The Qur’an was revealed in Arabic language onto the Prophet (PBWH), who was an inhabitant of a specific spacio-temporal world constituting its own social, cultural and historical horizon. The language of the Qur’an probably is the most important of its miraculous aspects and its distinct language in many verses. When scholars studied the Qur’an as a miracle however, its language and the style occupied the highest position in their studies. In early stages of Islam, scholars who dealt with the Qur’an and its interpretation considered it as a supernatural phenomenon and dealt with it from this perspective. Thus, this article attempts to discuss its definition, concept and principle from the views of prominent Muslim and Western Scholars such as Hamidu’l-Din Farahi, Amin Ahsan Islahi, Muhammad Arkoun, Schleiermacher, Dilthey, Heidegger, Gadamer, and F. A. Wolf in order to comprehend further about their philosophy of thought on the issues. Hermeneutics in global context seems a theory or philosophy of the interpretation of meaning. In this sense, there are threefold meaning might be used to display hermeneutics like ‘Hermeneutic as saying’, ‘Hermeneutic as explanation’ and ‘Hermeneutic as translation’ that describe the intellectual linguistic context of Qur’anic hermeneutics.